STABILITAS EPIGALOKATEKIN GALAT DALAM KRIM EKSTRAK TEH HIJAU DENGAN VARIASI KONSENTRASI ANTIOKSIDAN VITAMIN C 1% DAN VITAMIN E 1% - Nining Sugihartini; Hari Susanti; Zaenab Zaenab; Hana Hanifah; Siti Ayu Marlina (Sanata Dharma University, 2016)
Epigallocatechingallate (EGCG) in green tea extract has activity as an anti-inflammatory agent. On the other hand the stability of EGCG is poor because of the oxidation. The aim of this study was to determine the influence of Vitamine C and Vitamine E in formulation of green tea extract cream to the stabiliy of EGCG. The green tea extract was obtained from the extraction process by infundation followed by fractination with ethyl acetate as the solvent. The three formulas were compiled in similar composition with the concentration of vitamine C 1% (FI), Vitamine E 1% (FII) and there was no Vitamine C and Vitamine E (FIII) as a control. The EGCG level was determinated by TLC-densitometry methode. The stability parameter was determinated by calculated of the Q10 of each formula. The result of this study showed that the parameter of t90 of EGCG with Vitamine C 1%, Vitamine E 1% and control addition were 0.0108 hours, 0.0087 hours, 0.0084 hours, respectively. Stability of EGCG in green tea leaf extract cream with addition of the vitamin C 1% was higher than it stability with the addition of vitamin E 1%. The concentration of Vitamin C 1% was the optimum concentration as antioxidant in formulation of green tea extract cream.